The effect of single antiplatelet therapy on bleeding time during minor oral surgical procedure: a prospective study (Journal of Medical Sciences, 2022)
Background: antiplatelet agents have been widely used for the prevention and management of blood vessel thrombosis and heart stroke by preventing clot formation and platelet aggregation. On the other hand, antiplatelet drugs have also been related to an increase in bleeding time and risk of postoperative hemorrhage, so some dentists and surgeons still recommend the patient to stop the therapy for at least 3-7 days before any oral surgical procedures. Aim: the aim of this study was to evaluate the bleeding time with minor dental surgery in the patient on single antiplatelet drugs. Material and Method: Twenty patients who were planned for minor dental surgery (single dental extraction) were divided into two groups. In group A, patients on single antiplatelet therapy were included and in group B, patients who interrupted the drug before 2-3 days of procedures were included. The bleeding time of all patients was recorded before dental surgery. The minor oral surgery involved simple extraction of a single tooth under local anesthesia. The extraction socket was sutured with 0.3 silk and pressure pack gauze was given for at least 1h after extraction. Bleeding time after 1h and 24h was compared between two groups. A chi-square test was used to compare variables. Results: none of the patients showed active bleeding in the post-operative period. The results for postsurgical bleeding were statistically insignificant with P=0.05. Conclusion: minor dental surgical procedures especially single tooth extraction can be done without stopping of single antiplatelet therapy.